Nano-fluid viscosity screening and study of in situ foam pressure buildup at high-temperature high-pressure conditions - Hamza, M.F. (Springer, 2020)
In this study, an industrial-based surfactant known as MFomax surfactant has been modified with unfunctionalized and silane-functionalized silica nanoparticles (NPs) to select the high viscous nano-fluid (NF) for generation of in situ foam to assess the differential pressure buildup (âp) behavior in the porous media. Different weight concentrations of NPs and MFomax from 0.1 to 0.5 were studied using Design Expert Software to generate full matrix design of NF formulations. The viscosity data were analyzed with the aid of response surface analytical tool to investigate the response of NPs loading on the NF viscosity for optimization. The microstructural properties of the NFs were characterized using spectroscopic equipment. Subsequently, the high viscous NF was selected to generate in situ foam in comparison with the precursor MFomax foam for âp buildup assessment at 110Â Â°C and 2023 psi in the native reservoir core. Results have shown that both the silica NPs could significantly improve the MFomax viscosity; however, the silane-functionalized silica NPs have more effect to improve the viscosity and other microstructural properties than the unfunctionalized NPs, and thus, they were selected for further experimental studies. The coreflood âp buildup assessment shows that NF foam built more âp having average value of 46 psi against 25 psi observed in the case of the precursor MFomax foam. Thus, this study demonstrates that functionalized silica NPs could improve the MFomax viscosity and eventually generates high âp buildup at high-temperature high-pressure conditions. Â© 2019, The Author(s).